Reduced parahippocampal cortical thickness in subjects at ultra-high risk for psychosis. Issue 3 (10th May 2013) - Tognin, S.; Riecher-Rössler, A.; Meisenzahl, E. M.; Wood, S. J.; Hutton, C.; Borgwardt, S. J.; Koutsouleris, N.; Yung, A. R.; Allen, P.; Phillips, L. J.; McGorry, P. D.; Valli, I.; et al.
Abstract : Background: Grey matter volume and cortical thickness represent two complementary aspects of brain structure. Several studies have described reductions in grey matter volume in people at ultra-high risk (UHR) of psychosis; however, little is known about cortical thickness in this group. The aim of the present study was to investigate cortical thickness alterations in UHR subjects and compare individuals who subsequently did and did not develop psychosis. Method: We examined magnetic resonance imaging data collected at four different scanning sites. The UHR subjects were followed up for at least 2 years. Subsequent to scanning, 50 UHR subjects developed psychosis and 117 did not. Cortical thickness was examined in regions previously identified as sites of neuroanatomical alterations in UHR subjects, using voxel-based cortical thickness. Results: At baseline UHR subjects, compared with controls, showed reduced cortical thickness in the right parahippocampal gyrus ( p < 0.05, familywise error corrected). There were no significant differences in cortical thickness between the UHR subjects who later developed psychosis and those who did not. Conclusions: These data suggest that UHR symptomatology is characterized by alterations in the thickness of the medial temporal cortex. We did not find evidence that the later progression to psychosis was linked to additional alterations in cortical thickness, although we cannot exclude the possibility that the study lacked sufficient power to detect such differences.